Finance and Development, September 1981. (Finance and Development; Finance and Development, 1981)
This paper discusses the appointment of A. W. Clausen as the new World Bank president. Mr. Clausen, 57, joined the Bank of America in 1949 as a trainee just out of the University of Minnesota law school and rose to become president of the San Francisco-based institution 21 years later. His career at the Bank of America spanned 31 years, and he played an important role in the bank's expansion in the United States and overseas. Mr. Clausen has been bestowed many honors, including the Order of Merit of the Italian Republic.